Flanking Support: How Subsidiary Cells Contribute to Stomatal Form and Function - Gray, Antonia; Liu, Le; Facette, Michelle (Frontiers in Plant Science, 2020)
Few evolutionary adaptations in plants were so critical as the stomatal complex. This structure allows transpiration and efficient gas exchange with the atmosphere. Plants have evolved numerous distinct stomatal architectures to facilitate gas exchange, while balancing water loss and protection from pathogens that can egress via the stomatal pore. Some plants have simple stomata composed of two kidney-shaped guard cells; however, the stomatal apparatus of many plants includes subsidiary cells. Guard cells and subsidiary cells may originate from a single cell lineage, or subsidiary cells may be recruited from cells adjacent to the guard mother cell. The number and morphology of subsidiary cells varies dramatically, and subsidiary cell function is also varied. Subsidiary cells may support guard cell function by offering a mechanical advantage that facilitates guard cell movements, and/or by acting as a reservoir for water and ions. In other cases, subsidiary cells introduce or enhance certain morphologies (such as sunken stomata) that affect gas exchange. Here we review the diversity of stomatal morphology with an emphasis on multi-cellular stomata that include subsidiary cells. We will discuss how subsidiary cells arise and the divisions that produce them; and provide examples of anatomical, mechanical and biochemical consequences of subsidiary cells on stomatal function.